Pengaruh Content Quality, Social Media Engagement, dan Fear of Missing Out (Fomo) terhadap Impulsive Buying pada Produk Fashion di Tiktok Shop pada Generasi Z di Jakarta - Maulana Yusuf Wiarto; Corry Yohana; Ivan Putranto (Indo Publishing, 2026)
The research approach used in the study titled “The Influence of Content Quality, Social Media Engagement, and Fear of Missing Out (FOMO) on Impulsive Buying of Fashion Products on TikTok Shop Among Generation Z in Jakarta” was quantitative, employing a survey method. Data collection was conducted by distributing an online questionnaire to 150 respondents who are members of Generation Z in DKI Jakarta and have previously purchased fashion products through TikTok Shop. The sampling technique used a non-probability sampling method with purposive sampling, and employed a 6-point Likert scale measurement instrument. The data analysis technique used in this study was multiple linear regression analysis using IBM SPSS Statistics 27 software. The results show that Content Quality has a positive and significant effect on Impulsive Buying, Social Media Engagement has no significant effect on Impulsive Buying, and Fear of Missing Out (FOMO) has a positive and significant effect on Impulsive Buying. Collectively, these three independent variables explain 40.4% of the variation of Impulsive Buying (R² = 0.404; Adjusted R² = 0.392), while the remaining 59.6% is explained by other factors outside the research model. The practical implications of this study suggest that fashion businesses on TikTok Shop need to prioritize presenting high-quality, informative, and engaging content.